Encouraging Patients to Speak up About Problems in Cancer Care. Issue 8 (27th December 2021) - Mazor, Kathleen M.; Kamineni, Aruna; Roblin, Douglas W.; Anau, Jane; Robinson, Brandi E.; Dunlap, Benjamin; Firneno, Cassandra; Gallagher, Thomas H.
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: Many patients with cancer believe that something has gone wrong in their care but are reluctant to speak up. This pilot study sought to evaluate the impact of an intervention of active outreach to patients undergoing cancer treatment, wherein patients were encouraged to speak up if they had concerns about their care and to describe the types of concerns patients reported. Methods: Patients receiving cancer care at two sites were randomly assigned to an intervention or control group. Intervention patients received a brochure encouraging them to speak up about any concerns and an outreach telephone call during which the interviewer explicitly asked about concerns. Participants in both groups received baseline and follow-up questionnaires assessing their perceptions of their care and whether anything had "gone wrong" and provided ratings of health care providers' communication and responsiveness. Qualitative content coding was used to categorize patient-reported concerns collected through the baseline and follow-up questionnaires (both groups) and during telephone outreach (intervention patients only). The primary outcome was the number of patients reporting a concern about their care. Communication and responsiveness ratings for intervention and control group patients were compared using t tests. Results: Of the 60 patients in the intervention group, 34 (56.7%) reported at least one problem or concern, compared with 16 (29.1%) of the 55 patients in the control group ( P = 0.003). The telephone outreach in particular resulted in more than half of those reached reporting a new concern (55.3%). We detected no impact of the intervention on patients' ratings of communication or support for speaking up. Conclusions: Patients in this study reported a variety of concerns in response to active outreach, demonstrating that active outreach to patients can provide healthcare teams and systems the opportunity to offer a real-time response to the patient, identify where system improvements are needed, and implement policies, procedures, or programs to prevent recurrences.